Impact of Sarawak rainforest music festival attributes on visitors - Karimifar, Amir Reza (2013)
Among variety of different type of tourism attractions, festivals as short time events have a vast impact on local communities. Sarawak annual Rainforest World Music Festival in Malaysia is one of the unique events in the region which attracts thousands of music enthusiasts each year to the venue. However there is noticeable number of complaints about the festival those who have been to the festival complain about some festival services, shuttle buses to the venue, increasing prices of a hotel room or a festival ticket, and offensive behaviour of other visitors during the festival. Negative feedback may influence visitors’ loyalty whether to re-visit or recommend the event in the future. Studies have shown that high quality services will influence visitors’satisfaction and loyalty. However most of the studies have done in western cultures and every festival has its own dimensions. Also the impact of customer-to-customer interaction on visitors’ loyalty has never examined in the field of tourism events. This study examines the impact of attributes of the RWMF festival on visitors’ loyalty to the event. These attributes are motivations of Tourists toward festival theme, festival services, accommodations, transportations, and costumer-to-customer interaction. A survey questionnaire was distributed to the visitors of the Sarawak annual Rainforest Music Festival, and the data analyzed using Regression and factor analysis for investigating any relationship between constructs and ANOVA and t-test for any mean difference among defined groups based on demographic profile of the respondents. The results showed significant positive impact of motivations as the strongest determinant on visitors’ loyalty. This is the pull motivations of tourist toward the theme of the festival. Furthermore festival services such as entertainment programs, food and drink,information services, and ease of access also positively influenced visitors’ loyalty and finally costumer-to-customer interaction negatively influenced visitors’ future behavioural intentions. Based on the results Accommodation and transportation didn’t show any significant impact on the loyalty. Based on demographic profile of the respondents the results of the mean difference of the five studied dimensions were significant for level of income and history of visits. Managers of the festivals should pay considerable attention to the novelty and uniqueness of the characteristics of the event. Festival organizers must provide entertaining programs and variety of activities that can enrich the festival. Last implication for managers is the importance of controlling offensive interpersonal interactions among visitors to the festival.